ABOUT WELDMENTS FEATURE IN SOLIDWORKS - Cătălin IANCU (Fiabilitate şi Durabilitate)
In this paperwork are presented, based on example, details on Weldments feature in SOLDWORKS software. This feature allow the designer to model a weldment structure based on a 2D or 3D sketches for defining the basic structure of the part. The weldment structure is created by adding structural members joint in groups of similar members. By following steps presented here the designer can easily model even complex welded structures.